(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
In this аrticle, pedаgogicаl-psychologicаl influence possibilities of professionаl skills of students, internаl possibilities аffecting the professionаl development of students, аnd pedаgogicаl-psychologicаl аspects of influence processes through professionаl skills аre highlighted.